GAYA BAHASA PANTUN NIKAH KAWIN MASYARAKAT MELAYU BENGKALIS - Azmi, Ulul (Jurnal Ilmu Budaya, 2011)
'Pantun Nikah Kawin" is old literary work which still exists and develops in Bengkalis Malay sociery, it can be seen in wedding ceremof!Y, this Pantun is alwats used as a part ef the tradition. This Pantun Nikah Kawin which is found in Bengkalis Malay sociery has its own figure ef speech like prosody, diction, devices ef comparison like simile, metaphor, personification, hyperbole. Besides, it also consists ef repetitions like anfore, ephipore and respansion.